Review of lignocellulosic bio-chemical production: Current challenges, advances, and future perspectives - Bytyqi, Hysen; Mujdeci, Gamze Nur; Ekici, Ecrin; Ozturk, Abdullah Bilal; Madenli, Evrim Celik; Kumar, Gopalakrishnan (ELSEVIER, 2025)
Lignocellulosic biomass (LCB) constitutes approximately 90 % of the biomass of all plants on earth and is a highly promising green feedstock with the potential to be mass-produced industrially in the form of green biochemicals. Due to mounting climate change challenges and the depletion of fossil fuels, LCB has become a key priority in innovation hotspots aiming to lead the world toward a bio-based economy. Three predominant fractions of LCB-lignin, hemicellulose, and cellulose-pose vast opportunities but also corresponding challenging tasks in utilization. The progress in pretreatment technology, enzymatic hydrolysis, and fermentation has been such that the efficiency of conversion of LCB into biofuels, bioplastics, and value-added bio-chemicals such as ethanol, butanol, and organic acids is very high. High enzyme costs, lignin recalcitrance, and the production of inhibitory by-products are, however, problems that cannot be escaped. To this end, this review presents recent progress, current challenges, and prospects for future opportunities in the bio-chemical conversion of LCB with an emphasis on how it can contribute to achieving the world's sustainability targets. This review also provides an overview of advances in technology, including the development of microbial strains using CRISPR/Cas9 and consolidated bioprocessing (CBP) for process integration. Future directions, such as lignin valorization to more valuable chemicals and the incorporation of artificial intelligence for optimization, are highlighted. Policy measures, such as the EU Renewable Energy Directive and carbon-pricing legislation that enable LCB applications, are reviewed. Notwithstanding advances on the spectacular front, economic and technical issues, i.e., product recovery and pretreatment, are hindering uptake to the commercial level. Despite the remarkable advances on the front, economic and technical issues, i.e., product recovery and pretreatment, are hindering commercial adaptation. With international backing and policy support, LCB bio-chemicals have the potential to propel an industrial revolution, reduce carbon emissions, and lead the global bio-economy. Overall, this review provides a synthesizing critique of the novel data, points out critical gaps, and offers pragmatic recommendations for industrialization and future research areas.
Keywords: Lignocellulosic biomass; Bio-chemical production; Pretreatment technologies; Enzymatic hydrolysis; Lignin valorization; Circular bio-economy; VALUE-ADDED PRODUCTS; TECHNOECONOMIC ANALYSIS; ENZYMATIC-HYDROLYSIS; ANAEROBIC-DIGESTION; LACTIC-ACID; BIOLOGICAL PRETREATMENT; BIOETHANOL PRODUCTION; HYDROGEN-PRODUCTION; BIOFUEL PRODUCTION; ETHANOL-PRODUCTION; Energy & Fuels; Environmental Sciences & Ecology